A salinidade da água de cultivo afeta a qualidade e os aspectos sensoriais do camarão Penaeus vannamei? - Silva Junior, Wellington Lima da (2024)
Water salinity can alter the development, osmoregulation process and meat quality of shrimp, but there are few studies evaluating the interaction between salinity and the organoleptic quality of shrimp. Thus, the objective was to evaluate the physical-chemical parameters, meat quality, sensory aspects and purchasing power of shrimp meat raised in fresh, brackish and salt water. For this, shrimp (P. vannamei) cultivated in three types of salinity were evaluated: shrimp with 94 days old and cultivated in salinity of 0.32 ppt; shrimp with 87 days old and cultivated at a salinity of 22 ppt and; shrimp cultivated with 52 days old and salinity of 38 ppt. The loss of liquid due to thawing and cooking, the yield (%) of the shrimp fillet, as well as its texture, hardness, consistency, elasticity, gumminess and chewiness, as well as its color, were evaluated. Sensory analysis was carried out with 68 participants in order to verify their sensory quality and the quality index method for raw shrimp. The quantity of thermotolerant coliforms, Staphyloccus sp., was determined. and Salmonella sp. Fresh water shrimp showed (P<0.001) greater length, weight and fillet yield. Texture, hardness, gumminess and chewiness were higher (P<0.05), while muscle pH was lower (P<0.01) in shrimp cultured in saline waters. Fresh water shrimp showed greater luminosity and red tone (P<0.001). There was no difference in the growth of Salmonella sp., thermotolerant coliforms and Staphyloccus sp. depending on the salinity content. 1. It is concluded that Penaeus vannamei shrimp grown in water with low salinity showed better water retention, fillet quality, as well as better color and aroma. 2. Increased water salinity can negatively affect the quality of Penaeus vannamei shrimp meat. 3. In this research, water salinity did not affect microbiological parameters.